Analysis of Religious Moderation Messages for Generation Z in Gus Baha's Da’wah on Youtube - Ghulam Falach (Bahasa Indonesia, 2025)
Modern preaching using the development of technology has been widely used by several Indonesian preachers or da'i, one of whom is Gus Baha, whose da’wah are posted on YouTube. This has made his da’wah easily accessible to Generation Z, who are digital natives. Therefore, this study will further explore how Gus Baha's message of religiouse moderation is conveyed on YouTube and how Generation Z responds to these da’wah. Using the netnographicmethod, data was collected from primary sources in the form of transcripts of Gus Baha's da’wah on YouTube through documentation and observation techniques. Meanwhile, secondary data was obtained from journals, books, news articles and other relevant references. Holsti's content analysis model was used to process the data based on contextual units and recording units that answer the questions of what, to whom and how. This study found that Gus Baha'sda’wah are a response to religious conflicts, reducing extremism and restoring people's understanding of religious practices. His da’wah always reflect the stories of the Prophet and his companions, with references to the Qur'an, Hadith and other books, in a casual and straightforward style of everyday language. His da’wah are dominated by the themes of maintaining peace and adapting to local culture, and have been able to attract people through both their message and the use of the social media platform YouTube for preaching.